Failure failure failure failure failure failure: Six types of failure within the neoliberal academy. (May 2020) - Horton, John
Abstract: I am not a failure … but I feel like one and expect to fail every day of my working life within the neoliberal academy. This somewhat autoethnographic essay reflects upon six distinct, though related, feelings of failure which are everyday, axiomatic, but often-unspoken experiences of contemporary academic life. It considers failure in terms of: (i) things not going to plan; (ii) pervasive anxieties about performance within the neoliberal academy; (iii) regret, or wanting to do more; (iv) embodied senses of personal inadequacy and (not)belonging; (v) assessment criteria and procedures; and (vi) a vast, lucrative infrastructure of consultants, training organisations, entrepreneurial/leadership discourses and performative strategies which claim (triumph-over-)adversity as a kind of currency or capital to be deployed, monetised and enclosed. In so doing, this intervention opens a space to both acknowledge personal, embodied senses of failure and critically reflect on the Special Issue's aims of reclaiming failure within the contemporary neoliberal academy. The intervention ends with a series of questions which might serve as prompts for thinking-with failure and fostering more collegiate, critical ideas of success in the neoliberal academy. Highlights: Feelings of failure are a commonplace, everyday experience for many people working within the contemporary neoliberal academy. This intervention identifies six of the most pervasive forms of failure within contemporary academia. Reflective prompts are provided in support of more collegiate, critical ideas of success within the academy.